(untitled) - Hohenberg, Paul M. (Chicago, 1967)
Contents: Soda and related heavy chemicals; Coal-tar and oranic chemicals; Chemical fertilizers; Electricity and chemical processes
Keywords: Chemical industry,Công nghiệp hóa chất